Felipe and Claudette - Teague, Mark (New York Orchard Books, an imprint of Scholastic Inc., 2019)
Long time residents of Mrs. Barrett's adoption shelter, Felipe (a grumpy cat) and Claudette (a hyperactive dog) seem like they will never find a forever home, and Felipe is convinced that it is all Claudette's fault--but when the dog is finally adopted, Felipe is so depressed that he hides on adoption day, and it turns out that Claudette also misses her friend.
Keywords: Cats -- Juvenile fiction; Dogs -- Juvenile fiction; Friendship -- Juvenile fiction; Pet adoption -- Juvenile fiction; Animal shelters -- Juvenile fiction; Cats -- Fiction; Dogs -- Fiction; Friendship -- Fiction; Pet adoption -- Fiction; Animal shelters -- Fiction; Picture books